A randomized trial comparing empirical and guide therapy for unexplained non-cardiac chest pain - Kadir, Noor Purdah Abdul (2017)
Background Non-cardiac chest pain (NCCP) is prevalent in Malaysia with almost two-thirds a result of gastroesophageal reflux disease. Treatment approach to NCCP is currently unclear. We aimed to determine if therapy guided by results of 24-hour pH-impedance test would be better than empirical trial of PPI. Methods Consecutive participants with chest pain and normal angiogram or negative stress test were consented. Participants were randomized into guided group or empirical group. In guided group, all underwent 24-hour pH-impedance test (Sandhills, US) and if GERD then eight weeks of Dexlansoprazole 30mg OD but if functional chest pain or reflux hypersensitivity then four weeks of Theophylline SR 250mg OD were prescribed. In empirical group, two weeks of Dexlansoprazole 60mg OD were prescribed. Visual analog scale assessment (VAS) of chest pain, Gastroesophageal Reflux Disease Questionnaire (GERD Q), and Quality Of Life in Reflux And Dyspepsia (QOLRAD) questionnaire were evaluated during each visits at weeks 0, 2 and 8. Differences between visits were analyzed with Repeated Measures ANOVA. Results Of 200 screened patients, 145 did not meet inclusion criteria, and 55 randomized (26 empirical and 29 guided). A further 9 withdrew (5 empirical and 4 guided). No participants experienced serious adverse events. With RM-ANOVA, the results demonstrated that guided therapy did better than empirical therapy in mean VAS at week 2 vs. 0 and at week 8 vs. 0. The mean values of guided group were outside the confidence intervals of empirical group.Therefore, the mean VAS were significantly different. The results also demonstrated significant improvement of mean QOLRAD at week 8 vs. 0 in the guided therapy with p value=0.007, MD (95%CI) -3.2(-5.7,-0.8).However, no significant improvement in GERD Q were observed.In within-group analysis, mean QOLRAD was significantly better at week 8 vs. 0 (P=0.007) for guided group and for empirical group, mean QOLRAD was better at week 2 vs. 0 (P=0.004) and week 8 vs. 0 (P=0.01). On the other hand, mean GERDQ was better at week 8 vs. 0 (P=0.02) for empirical group only. We also observed that duration of treatment was the factor associated in the improvement of VAS in guided group. A duration of one week treatment would result in reduction of VAS scores by 0.7 points (95% CI -1.2, - 0.2; p=0.007). Conclusion In this analysis, guided therapy seems better than PPI trial in relieving chest pain symptom of NCCP patients. Both therapies improved QOL but those with GERD symptoms are better with PPI trial.